Lafarge truck design competition entries shortlisted - Rachel, Chew (The Edge Financial Daily, 2017)
KUALA LUMPUR: Judges of the Lafarge Malaysia #happinessinthecity Truck Design Competition have selected 14 entries to be in the running to win a total of RM6,000 in cash prizes.